Behavioral science in the global arena : global mental, spiritual, and social health - Congress, Elaine Piller; Meister, Dalton; Osborn, Shenae; Takooshian, Harold (International psychology (Charlotte, N.C.), 2022)
"This book focuses on global health - mental, spiritual, and social, three topics that are particularly relevant now that our world is struggling to survive the pandemic. At the United Nations we are very aware of the third sustainable development goal, the promotion of good health and well-being. Mental, spiritual, and interpersonal health are crucial in realizing this goal. Thus, we begin with looking at mental health around the world, then spiritual health in different faith traditions, and finally social health which includes interpersonal interactions within families and in communities. This second book in the UN book series continues with the three principal tenets of the UN Book Series. 1. The key current issues that affect our world are addressed. Since COVID 19 has had a devastating global impact, this book focuses on health. 2. As the problems facing our world are very complex, there is need for many voices from different disciples to address these challenging issues. Thus, this book includes authors from our professions of psychology and social work, as well as spiritual leaders, lawyers, and community activists 3. This book is co-edited and co-authored by students and recent graduates. Students have much to contribute beyond technological skills and generation of literature reviews. Thus, in this book they equally share in editorship and authorship of chapters. This book is written for anyone interested in global health. It should be of particular importance for faculty, students, practitioners who would like to learn more about current issues in global mental health as well as spiritual and social health"--